Identidade, trabalho e construção social da aposentadoria para ex-executivos - Adriana Ventola Marra (2013)
This thesis analyzed how former executives retired are reeonfiguring their identities from their identification processes and their meaning constructions for retirement, aging and work. The epistemological position adopted was that of social constructionism, which considers thatreality cannot be known in itself and asserts the existence of multiple realities constructed in the interactions between individuals. According to Gergen (1985, p. 266), research in social constructionism "focuses primarily on explaining the processes by which people describe, explain or interpret the world in which they live (including themselves)." The theoretical methodological option was discourse analysis. The statements referenced came from a corpus composed of twenty-three interviews and field journal. Patterns semantic evidenced in the Acorpus were: social constructions about retirement, work and its meanings, old age and identification with the institutional discourse. lirom these pathways, the constructions of meaning in the statements of the participants were analyzed with reference to the discursive strategies manifest: the creation of characters, the relationship between implicit and explicit themes, silencing, metaphors, lexical selection, interdiscourse and intradiscoursc. Throughout their lives, executives had prioritized their professional activities and left in the background their personal life. The overidentiiication of the executives with the organization institutionaldiscourse was linked to the overall centrality in the world of work, which made that their whole life stayed focus on their professional identity. Thus, the results indicated that executives generally didnt want and werent psychologically prepared for retirement. To deal with this new life phase, retired executives continued to keep busy, developing activities,whether prof`essional, voluntary or leisure, trying to reconfigure their identities, guided by attributes geared to maintaining the activity and youth. The fear of the weakness of old age combined with the retirement proved to be present in most discursive constructions of respondents. The reconfiguration of the identities of former executives was getting through the discursive construction of oppositions, about before and about after, their happy and well resolved retirements and the others unhappy retirements. These oppositions, prays reinforce and sometimes weaken, the identity borders between what they have been and what they are making them well-defined in a few moments and opaque in others. The use of the opposition discursive strategies helps in awareness of the condition itself. It is only when the retiree perceives the other as different that he becomes aware of his own identity. On duality objective identifications assigned by others and subjective identifications claimed by itself that they seek the recognition of others. The former executives retirees are reconliguring their own identity in a constant balance between being a retired and being away from everything that brought them power, status and recognition and what others expect them to be: active, dynamic and well resolved.